Kesetaraan Gender dalam Perekrutan Aparatur Sipil Negara Menempati Jabatan Struktural di Pemerintah Daerah Provinsi Nusa Tenggara Timur - Eugenia Natalia Meo; Veronika Ina Assan Boro (Perspektif: Jurnal Ilmu-ilmu Sosial)
The issue of gender injustice is a form of social injustice in Indonesia which has always been an interesting theme and will remain an important theme in every thought and conception of society in the future. This study aims to describe the recruitment process for ASNs in structural positions in the Provincial Government of East Nusa Tenggara and also the factors that influence the lack of female ASN occupying structural positions. The research method used is qualitative by collecting primary data through in-depth interviews and observation techniques, while secondary data is collected through archives and documentation. The results showed that the recruitment process for State Civil Servants to occupy structural positions was in accordance with the rules in the State Civil Apparatus Law No. 5 of 2014, although not fully implemented as a whole. Apart from the fact that regulations that have not been fully implemented have been identified as well as other factors that influence as well as a lack of interest or willingness from women themselves, space and opportunities are provided but awareness of women to take part is still very minimal.